It is over three decades of graduate education in epizootiology at the University of Ibadan, Nigeria (1975-2011): is there a need to revise the curriculum? (2012)
Epizootiology is the study of variable factors, events, forces and circumstances that contribute to the occurrence, distribution, control and prevention of ill-health, diseases and other problems in animal groups. It is a key component of veterinary medicine education at the University of Ibadan, Nigeria since 1975. It started as a Graduate Certificate in Epizootiology (GCE) in 1976. Later it was revised into M.Sc. Epizootiology in 1986. At graduate level, epizootiology curriculum has supported the M.Sc. Epizootiology programme. It compliments training in Veterinary Public Health and Preventive Medicine. This epizootiology curriculum has been operational at graduate level for more than three decades. Now in 2011, a consortium of English speaking West African Universities is committed to review the current curriculum at the University of Ibadan to strengthen health systems in an interdependent world with scope for internationalized practicum in disease investigation. Emphases are made towards skills development in molecular studies on disease causal agents and the mapping of associated geographic risk factors, including indigenous knowledge and practices. It is notable that most English-speaking West African countries including Ghana, Liberia, Sierra Leone and Gambia either lack a Veterinary School or just started some, but do not have graduate programme in Epizootiology. Thus, the curriculum at Ibadan is positioned to make impact in three key areas, namely, sub-regional ecosystem health studies, improving human-animal disease surveillance programmes, and in indigenization of bio-technology for monitoring and evaluation of trans-boundary animal disease control interventions for global health in West Africa